12m-5=11-5

Simple and best practice solution for 12m-5=11-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12m-5=11-5 equation:



12m-5=11-5
We move all terms to the left:
12m-5-(11-5)=0
We add all the numbers together, and all the variables
12m-5-6=0
We add all the numbers together, and all the variables
12m-11=0
We move all terms containing m to the left, all other terms to the right
12m=11
m=11/12
m=11/12

See similar equations:

| 9d=-8+5d | | x^2+4x+188=0 | | 16-2x=2x+14 | | x^2+4+188=0 | | 144=18/x | | -9-2f+10=9-f | | 16t/t-5=14/4 | | 4v-6=v+9 | | X+6=3x-3 | | 2^x+3=4^x-5 | | (-z+37)+(7z-85)=2(4z-41) | | -5m-6=6-3m | | -2(a-2)+5(a+3)=25 | | x=9,x=-3 | | 2=3/4x+5/4 | | 4t=32;t=8 | | 6z+1/9=7z+5/9 | | −8(−8x−6)=−6x−22 | | 5c+2=-c-8 | | 2=3/4r+5/4 | | 5t=t(t-4) | | (-6z+41)+(z+55)=2(-8z+59) | | 2−4x=−36 | | -2t-6=-t | | 9x+6x=7 | | 6-6x+42+7=0 | | 1-9v=-9v+4v+9 | | y/5+4=y/4 | | 5×-3.2=z | | (-s+8)+(7s+2)=2(-6s+23) | | 6s+2-4=10 | | -3.2×5=v |

Equations solver categories